Redes de conocimiento como estrategia de transferencia de tecnología para la adaptación al cambio climático (2018)
The impacts generated by the events of weather variability in the agricultural sector, evidence the low planning and implementation of adaptation measures that reduce the agro-climatic risk, added to the providers of agricultural technical assistance and producers´ little knowledge in this problem. The purpose of this work was to manage for the first time the structuring and training of a network of agricultural technical assistants in Boyacá that allowed to improve and appropriate the social management of knowledge, through the creation of communication links and technical strength, generating different spaces of interaction and participation; thus, it provides solutions to agro-environmental problems, from the local capacity and the inclusion of the climate-smart agriculture approach. The social analysis of the network was carried out in order to generate density and centrality indicators, showing the positions of the actors that make it up and it was evaluated the transference of knowledge acquired by the members of the network through the through the compilation of some experiences carried out by some of the members, it was framed in the management of environmental variables, risk management and the incorporation of technological options in order to improve the capacity and productivity of the production systems.